Effect of seeding on the microstructure and mechanical properties of alpha-SiAlON: I, Y-SiAlON - Zenotchkine, M; Shuba, R; Kim, JS; Chen, IW (AMER CERAMIC SOC, 2002)
The effect of seeding on the microstructure and mechanical properties of single-phase Y-alpha-SiAlON ceramics with elongated grains has been studied. Seeds of the intended alpha-SiAlON compositions but with different size, shape, and number of grains have been compared for their effects. The microstructure, resistance (R-curve) behavior, and Weibull modulus are strongly correlated to the number density of the seeds. The highest fracture toughness reached is similar to12 MPa.m(1/2) and can be obtained with as little as 1% seeding. The thermodynamic stability of seeds has been examined and is attributed to their chemical composition.
Keywords: SILICON-NITRIDE CERAMICS; LIQUID-PHASE; MORPHOLOGY; ALPHA' -SIALON; ALPHA-SI3N4; HARDNESS; CRYSTAL; GRAINS